Fostering the transfer of empirical engineering knowledge under technological paradigm shift: An experimental study in conceptual design. (August 2019) - Li, Xinyu; Jiang, Zuhua; Guan, Yeqin; Li, Geng; Wang, Fuhua
Abstract: Knowledge transfer is a frequently-used method for novice engineers to rapidly adapt themselves to a related new technological paradigm. However, due to different types in knowledge transfer, it remains divergent about the mechanism and motivation, leading to the chaos in tackling the low-quality and low-efficiency transfer process. This study concentrated on the individual-level transfer of empirical engineering knowledge (EEK) in product designers' mind triggered by technological paradigm shift, trying to accelerate the process and improve the result. Based on concept-knowledge model and eye-tracking data, this paper proposed a two-phase protocol and implements it in a practical case of conceptual design. Three factors of designers, prior cognitive level, utilization of the stimulus materials, and self-directed learning willingness, were evaluated and investigated. Results of 82 engineering students and young scholars showed that all three factors significantly impacted the validity and integrity of transferred EEK, and the efficiency of EEK transfer process. Specifically, key concepts in the stimulus materials, and creativity and initiative in learning willingness improved the validity and integrity. Non-essential words and too complex drawings lowered the efficiency. High cognitive level had side-effects on the transfer. These results inferred that the transfer of EEK could be fostered by wisely reusing past experience, selectively utilizing stimulus materials, and actively promoting learning willingness, which helps the designers to perform better in product design innovation.